Teaching Reading Comprehension by Using Crossword Puzzle Games for Junior High School Students - Vina Aisyah Zede (Universitas Veteran Bangun Nusantara, 2020)
The writer conclude that teaching reading comprehension by using crossword puzzle games method is very effective for junior high school students, specially to students of MTs Nurani. In this case, the method can improve the ability of students to love reading. The teacher is able to convey the material with intensive and capable of making students explore their thinking becomes more widespread. The influence of crossword puzzle games for the students is to increase knowledge in reading in English, and also to find the vocabulary that have never been on view, and also to increase the vocabulary knowledge of the students.